Savage Attack
1 online resource (xii, 294 pages)
Keywords: "In Savage Attack: Tribal Insurgency in India the authors ask whether there is anything particularly adivasi about the forms of resistance that have been labelled as adivasi movements. What does it mean to speak about adivasi as opposed to peasant resistance? Can one differentiate adivasi resistance from that of other lower castes such as the dalits? In this volume the authors move beyond stereotypes of tribal rebellion to argue that it is important to explore how and why particular forms of resistance are depicted as adivasi issues at particular points in time. Interpretations that have depicted adivasis as a united and highly politicised group of people have romanticised and demonized tribal society and history, thus denying the individuals and communities involved any real agency. Both the interpretations of the state and of left-wing supporters of tribal insurgencies have continued to ignore the complex realities of tribal life and the variety in the expressions of political activism that have resulted across the length and breadth of the Indian subcontinent."--Provided by publisher.